Low toxicity and long circulation time of Polyampholyte-coated magnetic nanoparticles for blood pool contrast agents - Wang, Qi (2016)
Polyampholyte-coated (poly(acrylic acid) (PAA)-co-3-(diethylamino)-propylamine (DEAPA)) magnetite nanoparticles (PAMNPs) have been prepared as contrasting agent used in magnetic resonance imaging (MRI). Excellent biocompatibility is required for contrasting agents used in high-resolution magnetic resonance angiography. To evaluate the biocompatibility of PAMNPs, some experiments have been conducted. The hemolysis, plasma recalcification, dynamic blood clotting, prothrombin time, inflammatory cytokine release and complement system activation assays were carried out to investigate the hemocompatibility. To evaluate the toxicity to vessel, MTT test and vascular irritation tests were conducted. Tissue toxicity test was also performed to investigate the biocompability in vivo. We also looked into the biodistribution. The results showed that PAMNPs at the working concentration (0.138 mM) present similar hemocompatibility with negative control, thus have no significant effect to vessels. PAMNPs were mainly distributed in the liver and the blood. The circulation time in blood was considerably long, with the half-time of 3.77 h in plasma. This property is advantageous for PAMNPs' use in angiography. PAMNPs could be metabolized rapidly in mice and were not observed to cause any toxic or adverse effect. In short, these results suggest that the PAMNPs have great potential to serve as safe contrast agents in magnetic resonance imaging (MRI).